Sramotilne kazni na Slovenskem - Makarovič, Gorazd (Etnolog. Nova vrsta (Ljubljana), 2011)
The article describes humiliating punishments and humiliation devices in Slovenia from the Late Middle Ages to the mid 19th century. It defines the social environments where these punishments originated and were carried out, and lists the offences subject to such penalties.
Keywords: ethnology; etnologija; history; zgodovina; humiliating punishments; kazniva dejanja; places of punishment; delikti; sramotilna kaznovanja; humiliation devices; prostori kaznovanja; humiliating marks; sramotilne naprave; sramotilna zaznamovanja; zgodovinski pregledi